Nutrient concentrations and distribution of phytoplankton pigments in recently deposited sediments of a positive tropical estuary. (July 2021) - Mathew, Jose; Singh, Archana; Gopinath, Anu
Abstract: Investigation of nutrients in the water column and phytoplankton pigments in recently formed modern sediments (0–5 cm) was carried out in Cochin estuary. The anthropogenic impacts were assessed using nutrients, nitrate, and phosphate in combination with phytopigments in sediments. The nitrate and phosphate concentration during the study ranged from 0.81 to 42.53 μmol/L and from 0.1 to 5.81 μmol/L, respectively. The mean values of the pigment showed the following order: zeaxanthin (791.53 ng/g) > lutein (347.57 ng/g) > fucoxanthin (335.30 ng/g) > pheophytin (308.84 ng/g) > pheophorbide (172.06 ng/g) > chlorophyll a (161.63 ng/g). The increase in the concentration of zeaxanthin indicated the presence of cyanobacteria, associated with eutrophication. Correlation analysis revealed that water column nutrients have a strong relationship between fucoxanthin and lutein, indicating the coexistence of diatoms and prasinophytes in the sampling sites. The principal component analysis showed positive loading of nutrients concomitant with pigment fucoxanthin and lutein, thus establishing that nutrient input controls the phytoplankton biomass of this estuary. Highlights: Zeaxanthin was the major carotenoid pigment indicating cyanobacteria community. Zeaxanthin was used as a marker for elucidating the eutrophic nature in the estuary. Nutrient enhancements were correlated with phytopigments in surface sediments. Fucoxanthin, indicative of diatoms was observed during the study period. Pheophorbide a and pheophytin a concentrations revealed zooplankton grazing and degraded phytodetritus.